STRATEGI BERTAHAN KELOMPOK AGAMA LOKAL - Nawari Ismail (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This study aims to understand the survival of local religious community from the government and muslim groups. The study employs ethnography design with qualitative approach. The study concerns on Wong Sikep in Pati. The data collections used are in-depth interview and participatory observation. The study applies purposive and snowball sampling. The results of the study show that local religious community survives because it is supported by objective and subjective structural condition. The objective structure that comes from Muslim consists of ethno-religiocentrism of Islamic groups, the weakening of Islamic missiology, lack of charismatic leaders in Islamic group, revitalization of religious tradition, and endogamy marriage system. Marriage, economics (agriculture), education, and language still exist. The other result reveals that strategies conducted by Wong Sikep exist through negotiation and resistance.